Tourism Development in Mountain Stations of Tamil Nadu: An Analysis of Eco-tourism and Sustainable Practices - Basariya, S. Rabiyathul (New Advances in Business, Management and Economics Vol. 2, 2025)
Background: Tourism has emerged as an instrument for employment generation, poverty alleviation, and sustainable human development. Tourism promotes international understanding and gives support to local handicrafts and cultural activities. It is an important segment of the country's economy, especially in terms of its contribution towards foreign exchange earnings, generation of additional income, and creation of employment opportunities. Aim: This study is an attempt to study the role of mountain stations in tourism development in Tamil Nadu to streamline it for more effective usage in the aspects of tourism as well as to enhance local development. Methods: The study was conducted via an analysis of tourism policy towards mountain stations from 2008-2013. The study reviews some selected documents on Tamil Nadu tourism and analyzes the data from inter alia the Tamil Nadu Tourism Development Corporation, 2012, India Tourism Magazine annual report, some academic journal articles as well as relevant websites. Results: The paper evaluates the progress of tourism development in selected mountain stations in Tamil Nadu through the policies of the Government of Tamil Nadu. In the context of the Influence of Adventure tourism activities, commonly mountain stations are the natural places with mountains lakes, forests, grasslands, etc., There is a great chance for Tamil Nadu to run various adventure activities. These may include inter alia hiking, trekking, boat racing, cycle riding, and hunting. Additionally, Tamil Nadu has great potential for the development of eco-tourism initiatives, especially given its cultural and natural diversity. Conclusion: Tamil Nadu has been significantly successful in its tourism efforts in creating a key platform for both domestic and international traffic. The entire region has vast untapped potential in tourism and its allied sectors, and there is a lot of scope for its future development and promotion.